Green engine coolant (GEC): cellulose nanocrystals as engine coolant process - D., Ramasamy; M. M., Rahman; K., Kadirgama; M. M., Noor; Azmi, W. H.; Mahendran, Samykano; W. S., Wan Harun (2018)
Today’s Thermal Transport Fluid has low heat transfer capacity due to low thermal conductivity value . Cellulose Nanocrystal (CNC) is a green and renewable material which is composed of nano sized cellulose fibril with a high aspect ratio. Dispersion of nanosized material enhance thermal conductivity but provokes three critical problem; high sedimentation leads to poor stability, hazards to the environment and dangerous to human health.